Pengaruh pH dan Rasio COD:N Terhadap Produksi Biogas dengan Bahan Baku Limbah Industri Alkohol (Vinasse) - Budiyono, Budiyono (Eksergi)
Industrial waste ethanol, which vinasse is one potential source to be processed into biogas. This study was conducted to assess the potential of vinasse waste and comparison nutrients needed to obtain biogas with optimum results. Experiments conducted in the digester volume 5L, operated at room temperature and neutral pH by varying the ratio of COD: N: P 800:7, 900:7, 1000:7 on vinasse mixture, rumen, urea and vinasse mixture , rumen, and NH4 HCO3  within 30 days. Respons which taken from this research are influence of pH, ratio of COD:N and nutrition to biogas production. The optimum condition of pH in producing biogas is at 7. Production of biogas produced at the optimum ratio of COD: N: P 800:7 is equal to 280 ml (0,96 ml biogas/mg TS COD) in a mixture of vinasse, rumen, urea and 3839 ml (13,73 ml biogas/mg TS COD) in a mixture of vinasse, rumen, NH4 HCO3  due to the comparison easier bacteria decompose organic compounds. While vinasse mixture, rumen, and NH4 HCO3  produces more biogas than vinasse mixture, rumen, urea may be due NH4 HCO3  to maintain the pH range so that the bacteria can survive.